Implementation Of Merdeka Curriculum In Public School In Menteng Central Jakarta - Gayatri Basuki; Masduki Ahmad; Siti Zulaikha (International Conference On Digital Advanced Tourism Management And Technology, 2023)
Based on research by the Indonesia Ministry of Education from January to April 2021, 3,391 elementary school (SD) students from seven districts in four provinces experienced significant learning loss in both literacy and numeracy. Due to the pandemic the learning loss experienced for numeracy was equivalent to five months of study and literacy was equivalent to six months of study. Merdeka Curriculum is a new policy established to develop students' potential character. One of them is the implementation of the Merdeka curriculum which is carried out in two Public Elementary Schools, Central Jakarta. There were five research subjects: the principal, deputy principal for curriculum, and teachers. The research was conducted using descriptive qualitative methods. The research results show that schools welcome the Merdeka Curriculum because it is pro-child. School principals and teachers try their best, starting from preparing the curriculum, teaching modules, implementing the learning process, to evaluating student competency. In the Merdeka Curriculum there is character education based on Pancasila values. However, the implementation of the Merdeka Curriculum was considered too hasty with a lack of socialization and training carried out by the education office and supervisors. Therefore, the Merdeka Curriculum needs to be prepared carefully by policy makers in order to prepare expert practitioners who can provide training directly according to teacher needs, so that teachers get clear information to develop themselves and improve their teaching abilities, as well as textbooks that should be adapted to student development.